Hydrodynamic characterisation of therapeutic glycan and glycan-like complexes - Alzahrani, Qushmua Eidan (2017)
Natural resources and plant extracts with therapeutic properties are considered important sources not only for food products, but also for the treatment of disease. Among edible herbal medicines are the gourd family or Cucurbitaceae, beta glucans, Nigella sativa and lignin. It is worth noting that after many research studies using a variety of screening, characterization and isolation methods that these glycan and glycan-like complexes have therapeutic components which have the ability to reduce the risk of many metabolic diseases. The properties of glycan and glycan-like complexes and the use as anti-diabetics were indicated. Although there have been great efforts made toward revealing the bioactive substances present in these materials, and several research studies have been undertaken, the bioactive components responsible are still not fully explored. The aim of this study is to explore further anti-diabetic properties and the hydrodynamic characterisation of glycan and glycan-like complexes obtained from Analytical Ultracentrifugation (AUC), viscometry, Dynamic Light Scattering (DLS) and Fourier Transform Infrared Spectroscopy (FTIR). Eliminating and analysis of fatty acids was performed in order to separate and purify protein-polysaccharide complexes from the family Cucurbitaceae and the complexes were also the target of investigation in this study. The value of sedimentation coefficient and a corresponding molecular weight yields a value for the frictional ratio ~ 13, suggesting a very high degree of hydration and asymmetry for the complexes in the family of Cucurbitaceae. The results of gas chromatography (GC) analysis indicate that polyunsaturated fatty acids (PUFAs) formed approximately 60% of the total oil from family of Cucurbitaceae which it is of high value in the human diet. The protein-like sedimentation profile of lipase adopts a polysaccharide like broad profile and sedimenting at a significantly faster rate suggesting all the lipase has bound to the beta-glucan. A plate shape structure for all three lignins with aspect ratio ~30:1 seems to be probable.